Primary Pelvic Hydatid Cyst: A Case Report - Fazl Q. Parray; Shadab Nabi Wani; Sajid Bazaz; Shakeel-ur Rehman Khan; Nighat Shaffi Malik (Case Reports in Surgery)
This is a case report of a young man who presented to us as a case of hypogastric pain and frequency of micturation. General physical examination and radiological evaluation confirmed a multiloculated pelvic swelling. Patient was subjected to laparotomy which confirmed the diagnosis of a primary pelvic hydatid disease. Patient was put on chemotherapy after surgery and is doing well on follow up.